Is insulin‐like growth factor‐I a good marker for treatment adherence in growth hormone deficiency in adulthood?. (23rd February 2016) - Auer, Matthias K.; Stieg, Mareike R.; Hoffmann, Janis; Stalla, Günter K.
Summary: Objective: There is a paucity of studies on adherence to growth hormone treatment in growth hormone deficient (GHD) adults. Therefore, this study reports on adherence to GH‐replacement therapy in adults with GHD, with a special focus on the course and potential predictors of nonadherence. Design: Retrospective single‐centre cohort study. Patients: From the local patient database, 179 suitable patients with GHD were identified. Measurements: The primary outcome was adherence assessed by calculating the percentage of available prescription data in comparison with recommended GH dosages over a mean follow‐up period of 92·4 months. Patients were categorized into five adherence categories ranging from <20% to >80%. Results: Mean overall adherence was 74·0%, with 52·9% of patients falling into the adherence group of >80% and 8·8% of <20%. There was a significant drop in adherence (9·8%) between the first and second years of treatment ( P < 0·001). Patients with childhood‐onset GHD were significantly less adherent to GH treatment than patients with adult‐onset GHD (62·0% vs 77·0%, P = 0·012); however, this finding was no longer significant after including age as a covariate. Frequency of IGF‐1 levels lying outside the age‐ and sex‐specific reference range was not a good indicator for adherence. Conclusion: Although overall adherence was relatively high in our study sample, there is a significant amount of patients who should be regarded as nonadherent. This applies in particular to younger patients. Treating physicians should be aware of the fact that IGF‐1 levels do not seem to be a good indicator for adherence.